Three-way cross designs for animal breeding experiments - HARUN, MOHD; VARGHESE, CINI; VARGHESE, ELDHO; JAGGI, SEEMA (The Indian Journal of Animal Sciences, 2016)
Three-way crossbreeding has been a major tool for the development of present day commercial breeds. The hybrids thus produced are more stable and they exhibit individual as well as population buffering mechanism because of the broad genetic base. Here, 2 methods of constructing designs for breeding trials involving complete/ partial three-way crosses were developed. Among these, first method is based on mutually orthogonal Latin squares, which yield three-way crosses arranged in blocks. The other method is derived from two-associate class partially balanced incomplete block designs. The efficiency factor in terms of information per cross pertaining to general combining ability effects of half parents as well as full parents in comparison to a complete triallel cross plan, assuming the error variance to be same for both the plans, was computed. All these designs have a good efficiency. Parameters of the designs constructed are listed together with the efficiency factors.